XMM-Newton Observations of the High Temperature Plasma in the Large Magellanic Cloud Supernova Remnant N132D - Adam R. Foster; Paul P. Plucinsky; Terrance J. Gaetz; Xi Long; Diab Jerius (The Astrophysical Journal)
We present an analysis of the archival XMM-Newton observations of the Large Magellanic Cloud (LMC) supernova remnant N132D totaling more than 500 ks. We focus on the high temperature plasma ( kT _e  ∼ 4.5 keV) that is responsible for the high energy continuum and exciting the Fe K emission. An image analysis shows that the Fe K emission is mainly concentrated in the southern part of the remnant interior to the region defined by the forward shock. This Fe K distribution would be consistent with an asymmetric distribution of the Fe ejecta and/or an asymmetric interaction between the reverse shock and the Fe ejecta. We compare the EPIC-pn and EPIC-MOS spectra in the 3.0–12.0 keV bandpass with a model based on RGS data plus a higher temperature component, in collisional ionization equilibrium (CIE), or nonequilibrium (both ionizing and recombining). We find that the data are equally well fitted by the CIE and ionizing models. Assuming the CIE and ionizing spectral models, the Fe in this high temperature component is significantly enhanced with respect to typical LMC abundances. We can place only an upper limit on the neutral Fe K line. We conclude that the Fe K emission is due to ejecta heated by the reverse shock given the spatial distribution, relatively high temperature, and enhanced abundance. We estimate the progenitor mass based on the Ca/Fe and Ni/Fe mass ratios to be 13 ≤ M _P ≤ 15 M _⊙ .